Gender diversities – practising intersectionality in the European Union. (August 2014) - Agustín, Lise Rolandsen; Siim, Birte
This article analyses the European Year for Combating Poverty and Social Exclusion (2010) (EY 2010) with the aim of identifying the nature of gender diversities in European Union policies. We argue that the European Union handles issues related to gender and diversity in particular ways; this approach is characterised by non-citizen/citizen and redistribution/recognition divisions. Employing intersectionality as the methodological approach to gender diversities, the article shows how gender and ethnicity are articulated in the policy-making process which led to the adoption of EY 2010, the activities undertaken during EY 2010 and the evaluation of EY 2010. The case study is suitable for developing a dynamic multi-level model for analysing gendered diversities at the transnational level: It illustrates how the EU policy framework interacts with particular national contexts in promoting or hindering the advancement of policy contents which pay attention to the intersection between gender and diversity.